The Role of Financial Literacy and Fintech in Sharia Financial Inclusion: A Case Study in Babadan Ponorogo - Laila Husna Zahratul Muna; Ratna Yunita (Niqosiya: Journal of Economics and Business Research, 2025)
Introduction: Financial inclusion is the availability of public access to financial services products that suit their needs. Islamic financial literacy and financial technology are factors that can affect the level of financial inclusion. If Islamic financial literacy and financial technology increase, Islamic financial inclusion will also increase. However, in reality, the results of interviews with several people in Babadan District, Ponorogo Regency, show that increasing Islamic financial inclusion is not accompanied by good Islamic financial literacy and financial technology. The purpose of this study is to analyze the influence of Islamic financial literacy and financial technology on Islamic financial inclusion. This study uses a quantitative research approach. The sampling technique in this study is probability sampling. Sampling in this study, using the Slovin formula, a sample of 100 respondents was obtained. The results of the study show that Islamic financial literacy has no effect on Islamic financial inclusion. This is evidenced by the results of the t-test. Financial technology has a significant positive effect on Islamic financial inclusion. Islamic financial literacy and financial technology simultaneously have a significant positive effect on Islamic financial inclusion. The regression model is declared feasible because it can significantly explain variations in dependent variables.